Holocord syringomyelia in 18 dogs - Douralidou, Despoina; Mari, Lorenzo; Wyatt, Sophie; Minguez, Juan Jose; Fernandez, Patricia Alvarez; Anselmi, Carlo; Posporis, Christoforos (Frontiers in Veterinary Science, 2025)
Holocord syringomyelia (HSM) is characterized by a continuous spinal cord cavitation along its entire length and is currently poorly documented in dogs. This retrospective multicentric case series investigates the clinical and MRI findings in 18 dogs with HSM. The median age at presentation was 82 months (range 9–108 months) and French Bulldogs were overrepresented (50%). Signs of myelopathy attributed to HSM were detected in 12 dogs (67%), spinal pain/paresthesia/allodynia in eight (44%), and four dogs (22%) had no HSM-associated signs. The most common neuroanatomical localization was C1-C5 spinal cord segments. On MRI, the cranial limit of HSM was at C1 vertebra in seven (39%) and at C2 in 11 dogs (61%). The caudal limit extended to L3 in four dogs (22%), L4 or L5 in six dogs (33%) each, and L6 in two dogs (11%). The conus medullaris terminated at L5 in one dog (6%), L6 in 11 (61%), and L7 in six dogs (33%). Seventeen dogs (94%) exhibited MRI features of Chiari-like and/or other intracranial/cranio-cervical junction malformations. One dog (6%) was treated surgically, 11 (61%) medically, and six (33%) received no treatment. Over a median follow-up of 12 months (range 2–65 months) in 16 dogs, one dog (6%) improved, nine (56%) deteriorated, four (25%) were static, and two (13%) remained free of HSM-associated signs. This is the first study to describe canine HSM, highlighting a possible breed predisposition in French Bulldogs. The frequent occurrence of myelopathy and disease progression underscores the need for further research into the underlying etiopathogenesis, natural disease evolution, and response to therapeutic interventions.